2019
DOI: 10.7759/cureus.3970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Chronic Obstructive Pulmonary Disease in Bangladesh: A Systematic Review

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and morbidity in low- and middle-income countries (LMICs) including Bangladesh. But no systematic review has been carried out in Bangladesh, which portraits the burden of COPD and its risk factors. Therefore, this systematic review was conducted to find out the prevalence and risk factors of COPD in Bangladesh. We searched PubMed, Google Scholar, Popline, and Banglajol from January 1, 1972 to April 30, 2017. We included studies that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 41 publications
7
48
0
Order By: Relevance
“…28,29 We found a significantly higher prevalence and also the odds of COPD among current smokers compared to never smokers, in line with previous studies. 30,31 Similar to previous studies, 16,21,32 biomass fuel consumption was found significantly associated with higher odds of having COPD. Biomass smoke is an important contributor to household air pollution that leads to COPD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…28,29 We found a significantly higher prevalence and also the odds of COPD among current smokers compared to never smokers, in line with previous studies. 30,31 Similar to previous studies, 16,21,32 biomass fuel consumption was found significantly associated with higher odds of having COPD. Biomass smoke is an important contributor to household air pollution that leads to COPD.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence reported in this study is marginally lower than the earlier national-level estimation of 9.8% based on predictive covariates, 12 and significantly lower than the 11.7% estimation using the GOLD criteria. 9 Likewise, the identified prevalence is also lower than the estimate from neighbouring countries Bangladesh (12.5%) 21 and Pakistan (11.3%) 22 but similar to the prevalence reported in studies conducted in India (4.1% to 9%) 23 and the BOLD study China (8%). 11 However, in most of the epidemiological surveys, COPD is defined based upon spirometry data only.…”
Section: Discussionsupporting
confidence: 82%
“…As a result, it supposedly faces a significant challenge in implementing any health measures. Besides, many senior citizens and mid-aged people in the country have non-communicable disorders, including chronic obstructive pulmonary disease (11.9%), cardiac disorders (4.5%), diabetes (9.7%), and asthma (5.2%) (26)(27)(28)(29). These people with multiple comorbidities are also especially vulnerable to emerging infectious diseases, e.g., the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Bangladesh also falls in the category of unfortified countries due to its high population and poor health care system [12]. A total of 7% of the county's population are senior citizens [13]. Most of these senior citizens, as well as middle-aged people in the county, have comorbidities, such as diabetes (9.7%), asthma (5.2%), hypertension (20%), cardiac disease (4.5%) and chronic pulmonary disease (11.9%), and around 1.3 to 1.5 million cancer patients in the country are vulnerable to COVID-19 [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%